Analysis of Dollarization Hysteresis among North Korean Consumers - Jooyung Lee (East Asian Economic Review (EAER), 2022)
This paper quantitatively analyzes the current status of North Korean consumer payment instruments through a questionnaire survey of 292 North Korean defectors. In the 2010s, it was found that the payment experience ratio of domestic currency cash and grain decreased, while the payment experience ratio of foreign currency cash increased. The use of foreign currency reached a stage where it was spread not only as a store of value but also as a medium of exchange. However, the most frequently used payment instrument by North Korean consumers was still domestic currency cash. By region, in inland urban areas both domestic currency cash and U.S. dollars are used and in the North Korea-China border region both domestic currency cash and Chinese yuan are used, while in inland rural areas dollarization does not occur because both domestic currency cash and grain are used. Meanwhile, despite the stable price trend during 2013-2019, the dollarization hysteresis effect is appearing, and both the purchasing power risk theory and the network externality theory are considered to have explanatory power for the cause. The results of this paper suggest that as dollarization is intensifying, it is expected that more costs such as shortages of commodities will be incurred than in the past if North Korea's de-dollarization policy is reimplemented. Also, in the case of domestic currency cards, which the North Korean authorities introduced in 2015 as part of a means of financial reform, this paper suggests that it may continue to be difficult for domestic currency cards to normalize official finance under the dollarization hysteresis.
Keywords: F31; G50; O57; 330; North Korean Consumers; Payment Instrument; Dollarization Hysteresis